PENGEMBANGAN KEMANDIRIAN ANAK YANG DIBESARKAN DI PANTI ASUHAN (STUDI KASUS DI PANTI ASUHAN KRISTEN GMIT 221 KUPANG) - Suy, Sofi; Pareira, Mariana Ikun RD; Lima, Stofiani Susana (Universitas Nusa Cendana, 2024)
ABSTRACT This research was conducted to describe the process of developing independence for children raised in the GMIT 221 Kupang Christian orphanage. This research uses a qualitative case study approach. The subjects in this research were 3 children from an orphanage and one caregiver. Data collection was carried out using observation techniques, interviews and documentation studies. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The results of this research show that (1) in the responsibility stage where caregivers play a very important role in the process of developing children's independence. (2) In this autonomy stage, the caregiver always provides direction in carrying out tasks so that children feel confident in carrying out tasks according to their respective groups. (3) This initiative stage is where caregivers always provide opportunities for children to carry out activities outside the orphanage such as operating the LCD in the church and attending worship every morning and evening. (4) This stage of self-control is where children are able to control themselves in overcoming the problems they face and children are able to make decisions The conclusion of this research is that with the activity schedule in the orphanage, it can be seen that there is a positive change in every child in the orphanage where at first they were not able to do their own tasks, but with the assistance and supervision of the caregiver over time the children are used to doing things themselves so that children become independent.